2003
DOI: 10.1002/cncr.11679
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in cervical cancer

Abstract: Cervical cancer traditionally has been staged clinically. Advances in imaging could improve the staging of cervical cancer by facilitating the detection of lymph node metastases and micrometastases in distant organs. Such progress could lead to improvements in treatment selection and therefore increase overall survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 61 publications
(78 reference statements)
2
66
0
4
Order By: Relevance
“…In the assessment of primary cervical cancers, the value of MRI is well documented [4,5,16,17]. More recently, increasing amounts of data also have shown that 18 FDG PET may detect an intense metabolic signal at the level of the primary site with a high sensitivity (81-100%) [10,11,12,13,14,18,19,20]. When the performances of both imaging modalities were compared in a prospective series including 22 patients with histologically proven cervical cancers, a similar sensitivity of 91% was found.…”
Section: T Stagingmentioning
confidence: 83%
See 3 more Smart Citations
“…In the assessment of primary cervical cancers, the value of MRI is well documented [4,5,16,17]. More recently, increasing amounts of data also have shown that 18 FDG PET may detect an intense metabolic signal at the level of the primary site with a high sensitivity (81-100%) [10,11,12,13,14,18,19,20]. When the performances of both imaging modalities were compared in a prospective series including 22 patients with histologically proven cervical cancers, a similar sensitivity of 91% was found.…”
Section: T Stagingmentioning
confidence: 83%
“…This includes the detection of the initial tumour site and its precise delineation in a three-dimensional space. Also critical is the assessment of prognostic variables such as the depth and width of stromal invasion, local extension into the vagina or the parametrium, as well as the spread of the tumour into the pelvic wall and beyond into the bladder and/or the rectum [1,2,13,15]. In the assessment of primary cervical cancers, the value of MRI is well documented [4,5,16,17].…”
Section: T Stagingmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Intensity modulated radiation therapy (IMRT) enables definitive treatment of para-aortic target volumes with escalated doses of radiation while simultaneously sparing the adjacent organs at risk including the small bowel, spinal cord, and kidneys. [6][7][8][9] Though IMRT for postoperative pelvic radiation treatment for cervical cancer is well established, conventional 3-D conformal fourfield pelvic RT remains a standard of care and is often preferred for intact cervical cancer.…”
Section: Introductionmentioning
confidence: 99%